The Afghanistan papers : a secret history of the war - Whitlock, Craig
"The groundbreaking investigative story of how three successive presidents and their military commanders deceived the public year after year about the longest war in American history by Washington Post reporter Craig Whitlock, a three-time Pulitzer Prize finalist"--
A Muddled Mission -- "Who Are the Bad Guys?"-- The Nation Building Project -- Afghanistan Becomes an Afterthought -- Raising an Army from the Ashes -- Islam for Dummies -- Playing Both Sides -- Lies and Spin -- An Incoherent Strategy -- The Warlords -- A War on Opium -- Doubling Down -- "A Dark Pit of Endless Money" -- From Friend to Foe -- Consumed by Corruption -- At War with the Truth -- The Enemy Within -- The Grand Illusion -- Trump's Turn -- The Narco-State -- Talking with the Taliban.
Includes bibliographical references and index.
Keywords: Afghan War, 2001-